Simultaneous supratentorial and brainstem abscesses due to Listeria monocytogenes. - Soares-Fernandes, JP (2008)
Multiple supratentorial abscesses caused by Listeria monocytogenes are rare. We report the simultaneous occurrence of multiple supratentorial and brainstem abscesses due to Listeria, in a patient under corticotherapy for an exacerbation of ulcerative colitis. MR imaging features before and after successful conservative treatments are depicted. In immunocompromised patients with supratentorial listerial abscesses, the coexistence of brainstem abscedation is exceptional. Despite high mortality associated with listerial abscesses, this case illustrates the possibility of a good clinical outcome, if the appropriate antibiotic regimen is instituted and the immunosuppressant agent is discontinued.